Analyzing the Arabic Translation of ‘The King and the Handmaiden’ in Rumi's Masnavi Based on Viney and Adrbelnet’s Model (A Case Study of the Poetic Translation by Hashemi and Jawaheri) - Aliasghar Shahbazi; Mostafa Parsaeipour (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2020)
Rumi's Masnavi has been widely popular outside the Persian culture, having attracted many an audience. The work has been warmly welcomed in Arabic cultures as well. Arabic literary figures have provided several translations of this literary-mystic masterpiece in prose and poetry, among which the poetic translations of two contemporary Arab poets, Abdul Aziz Jawaheri and Mohammad Jamal Hashemi, have served a key role in introducing Masnavi to the Arab audience. Translators’ familiarity with Rumi’s philosophy and cultural affinity between the source and target cultures have helped reflect the spiritual atmosphere of the poems in Arabic. Having discussed the qualitative characteristics of these translations, the study has investigated the translations of the first story in Rumi’s Masnavi, The King and the Handmaiden, within the procedures provided by Viney and Darbelnet. The results show that Jawaher’s translation is closer to the original, adopting direct translation procedures, particularly ‘literal translation’, more extensively. Faithfulness to the source text is yet another virtue of this translation. Hashemi has provided a translation that mostly reveals the syntactic and pragmatic elements of the target language, explicating many elements to make the text more accessible to the readers in lieu of literal translation. Among the seven procedures studied, transposition and modulation are significantly more prevalent than others.